HUMANITIES IN A REGIONAL UNIVERSITY - Robert H. Kochesokov; Zukhra A. Kuchukova (Высшее образование в России, 2017)
The article highlights a contradictory situation connected with the state of social sciences and Humanities in regional university: on one hand, they must be oriented on the regional ontology, on the other hand - on Russian and world problematic and thematic trends. The example of Kabardino-Balkarian State University shows that optimal correlation of regional, i.e. particular and single with general in social genesis allows regional researches to reveal new perspectives and horizons of social and cultural being - Russian and global. The most fruitful can be considered scientific research in the framework of collective projects and within the paradigm of interdisciplinary approach (with participation of philosophers, historians, cultural scientists, philologists, psychologists); cooperation with the leading Universities and scientific institutes; preparation and publication of special thematic issues of the leading Russian scientific journals as well as organization and holding of thematic conferences jointly with the leading scientific institutions.